2018
DOI: 10.1002/poc.3823
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity in heterocyclic analogues of benzene: Dissected NICS and current density analysis

Abstract: The magnetic aromaticity of 6‐membered monoheterocycles containing Group 13 to 16 elements (C5H5X, where X = SiH, GeH, N, P, As, O+, S+, Se+) was assessed by using 2 magnetic descriptors: the π‐electron contribution to the out‐of‐plane component of the nucleus‐independent chemical shifts (NICSzz,π) and ring current strength. The results show that both descriptors lead to the same conclusion regarding magnetic aromaticity. However, they do not agree with the predictions obtained by isotropic NICS, which is a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…66 It has been demonstrated that NICS pzz in addition to NICS zz (1) could be the most reliable aromaticity indexes, with statistically good correlation with aromatic stabilization energies. 64,69 The NICS zz values of 3 [NICS zz (1) (1)…”
Section: Methodsmentioning
confidence: 99%
“…66 It has been demonstrated that NICS pzz in addition to NICS zz (1) could be the most reliable aromaticity indexes, with statistically good correlation with aromatic stabilization energies. 64,69 The NICS zz values of 3 [NICS zz (1) (1)…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies, based on ring currents strengths and NICS zz evaluations, suggest that all pnictogen heterobenzenes are strongly aromatic; moreover, their aromaticity decreases as the heteroatom size increases. [25] As we can see in Figure 4, all the C 5 H 5 X (where X = N, P, As, Sb, Bi) systems are less aromatic than benzene, but they remain strongly aromatic with bifurcation values between À 35 and À 45 ppm for bismine and arsinine, respectively. However, the order of aromaticity (predicted by the bifurcation value) does not follow a periodic trend.…”
Section: Methodsmentioning
confidence: 80%
“…The Bznormalinormalnnormald , has been analyzed using different strategies. For instance, two‐dimensional maps have been used by several authors to describe the electronic delocalization,, and, more recently, the chemical bond in different compounds. These maps provide more detail regarding the delocalization of various systems and have been applied qualitatively to describe aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used to study the electron delocalization in bonds and molecules . Moreover, this vector field has been extensively used to study and evaluate one of the most important concepts in chemistry, the aromaticity . This concept is not a physical observable, therefore, several indices based in the geometric, energetic, electronic, and magnetic properties have been proposed to evaluate it .…”
Section: Introductionmentioning
confidence: 99%